A kind of anti-cracking and anti-corrosion concrete and preparation method thereof

Through the multi-step treatment of kitchen residues, cement and fly ash, it forms a porous structure, and combines materials such as hexaethylcyclotrisiloxane to solve the cracking and corrosion problems of concrete in the salted area, achieving cracking and anti-cracking and prevention Corrosion effect.

CN118026590BActive Publication Date: 2024-12-27TIBET KUNNENG COMMERCIAL MIXING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311793839.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2024-12-27
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

Existing concrete is prone to cracking and corrosion problems when applied to coastal, coastal salted areas and other areas, resulting in corrosion of steel bars and is difficult to effectively prevent.

Method used

The crushing, fermentation and heat treatment of kitchen residues, cement and fly ash is used to form a porous structure, and the crushing and dilute nitric acid grinding is carried out through high-temperature CO2 airflow to form ultrafine fillers to improve crack resistance and corrosion resistance. At the same time, hexaethyl ring three is used Materials such as silicone enhance the bonding force and tough network structure of concrete.

Benefits of technology

The anti-cracking and corrosion resistance of concrete is achieved, extending the rust time of steel bars, slowing down the corrosion speed, and improving the anti-cracking and corrosion resistance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004627121590000081
    Figure BDA0004627121590000081
Patent Text Reader

Abstract

The invention discloses a crack-resistant and corrosion-resistant concrete and a preparation method thereof, and relates to the technical field of concrete. The invention first uses kitchen residues, cement and fly ash as raw materials, and undergoes heat treatment to achieve semi-carbonization, thereby obtaining an aggregate-like filler with apparent strength and certain toughness inside, thereby improving the anti-cracking effect of the concrete, and then undergoes secondary activation and secondary grinding modification to obtain a hydroxylated ultrafine filler containing an inorganic rust inhibitor, which can effectively control the release of the inorganic rust inhibitor and achieve the anti-corrosion effect of the concrete; then, after the pre-emulsion precursor is preliminarily mixed with coarse and fine aggregates, raw materials such as cement and ultrafine fillers are added respectively, and the pre-emulsion precursor forms a tough mesh structure inside the concrete, thereby further improving the crack resistance of the concrete, and at the same time, the ultrafine filler is adsorbed on the surface of the mesh structure, and self-stacks, gradually expanding the mesh structure, thereby further improving the anti-corrosion and anti-cracking performance of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, in particular to anti-cracking and anti-corrosion concrete and a preparation method thereof. Background Art

[0002] When concrete is used in coastal areas, coastal saline land, inland salt lake areas and other areas, the soil in these areas has high content of chloride ions and sulfate ions, which can penetrate or activate the oxide protective film on the surface of the steel bars, thereby creating conditions for electrochemical corrosion. The electrode potentials of various parts of the steel bars will be different, forming local batteries. Once the corrosion of the steel bars occurs, it will continue.

[0003] Existing concrete is prone to cracking during the preparation and use processes. When the concrete solidifies and hardens, the free water inside gradually evaporates from the surface to the inside, causing the concrete to gradually dry and shrink from the surface to the inside. When the tensile stress generated by the shrinkage is greater than the tensile strength limit of the concrete component, the concrete will crack. Summary of the invention

[0004] The purpose of the present invention is to provide a crack-resistant and corrosion-resistant concrete and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing anti-cracking and anti-corrosion concrete, comprising the following preparation steps:

[0006] (1) Kitchen residues are sorted, bones are removed, and the residues are fed into a press to obtain wet materials, cement of 0.3 to 0.5 times the mass of the wet materials and fly ash of 0.9 to 1.6 times the mass of the wet materials are added, and the residues are fed into a crusher to be crushed to a particle size of 1 to 3 mm, and granulated to obtain an intermediate A of 5 to 10 mm in diameter; the bacterial liquid and the intermediate A are mixed at a mass ratio of 1:1000, fermented at 37 to 55° C., 80 rpm, and a ventilation volume of 4 to 8 L / min for 48 to 72 h, dried at 100° C. for 10 h, and then heated to 200 to 250° C. , semi-carbonized for 4 to 8 hours, put into a jet mill, crushed for 20 to 30 minutes, taken out, activated at 400 to 500°C for 20 to 30 minutes in an atmosphere of 15% by volume carbon dioxide-nitrogen, to obtain intermediate B; intermediate B and nitric acid solution were mixed at a mass ratio of 1:3, the ball-to-material ratio was 15:1, and the grinding speed was 150 to 250 rpm for 10 to 25 minutes, and then a sodium nitrite aqueous solution 3 to 5 times the mass of intermediate B was added, and the grinding was continued for 10 to 25 minutes, filtered, and dried at 100°C for 6 hours to obtain an ultrafine filler;

[0007] (2) Under stirring at 300 rpm, add the pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 50-80°C for 1-2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 50-70 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete.

[0008] Furthermore, in step (1), the press is used to press the soil until the moisture content is between 20% and 30%.

[0009] Furthermore, the bacterial solution in step (1) is composed of Geotrichum candidum, lactic acid bacteria, white rot fungi, and Aspergillus niger in a volume ratio of 1:1:1:1, and the bacterial content is (1-9)×10 12 Pieces / mL.

[0010] Furthermore, in step (1), the powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.8-1.0 MPa.

[0011] Furthermore, the airflow of the airflow mill in step (1) is 15% carbon dioxide-nitrogen at 200°C.

[0012] Furthermore, the mass fraction of the nitric acid solution in step (1) is 15-35%.

[0013] Furthermore, the mass fraction of the sodium nitrite aqueous solution in step (1) is 4%.

[0014] Furthermore, the preparation method of the pre-emulsion precursor in step (2) is: mix hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, perchlorate O-25, and deionized water in a mass ratio of 50:20:0.5:80 to 50:30:0.5:95, stir at 600 rpm for 15 to 30 minutes, and homogenize at a pressure of 30 MPa for 1 minute.

[0015] Furthermore, in step (2), the mass ratio of the coarse aggregate, the pre-emulsion precursor, the cement, the fine aggregate, the ultrafine filler, the microsilica powder and the deionized water is 350-550:25-35:100-150:150-320:80-120:4-8:160-180.

[0016] Furthermore, the particle size of the microsilica powder in step (2) is 0.1-0.5 μm, and the silicon content of the microsilica powder is above 93%.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0018] The present invention prepares concrete by mixing ultrafine filler, pre-emulsion precursor, cement, aggregate, microsilica powder and the like to achieve the effects of crack resistance and corrosion resistance.

[0019] Firstly, the present invention utilizes kitchen residues, cement and fly ash to be pulverized, fermented and granulated together, and after heat treatment, moisture and volatile substances are gasified, and part of the internal organic matter is decomposed to achieve semi-carbonization, a porous carbonized layer appears on the surface of the particles, while the toughness is retained inside, which can improve the anti-cracking effect of concrete; then the first grinding is carried out, and high-temperature CO2 airflow is used for pulverization, and the particle size is refined and initially activated at the same time, and then the CO2 temperature is further increased to enrich the number of micropores and form a porous structure, and then a secondary grinding is carried out, and dilute nitric acid and an inorganic rust inhibitor aqueous solution are used as grinding media in turn to increase the active groups such as hydroxyl and carboxyl on the surface of the ultrafine filler, and at the same time, through the capillary action of the surface pore size, the inorganic rust inhibitor is adsorbed in the pores of the ultrafine filler, effectively controlling the release of the inorganic rust inhibitor, which can delay the time when the steel bar starts to rust, slow down the speed of steel bar corrosion development, and achieve the anti-corrosion effect of concrete.

[0020] Secondly, the present invention utilizes hexaethylcyclotrisiloxane and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine to prepare a pre-emulsion precursor. After being mixed with cement and aggregate, part of the silicon-oxygen bonds are combined with the cement and aggregate surfaces, which is beneficial to enhancing the internal bonding force of the concrete and improving the crack resistance of the concrete. After heat treatment, the polymer forms a tough network structure. When the concrete is subjected to force and is about to crack, the cement separation is inhibited through the pulling effect of the network structure, and the anti-cracking performance of the concrete is improved. In addition, with the continuous addition of raw materials such as stirring and ultrafine fillers, the ultrafine fillers rely on surface active groups to generate hydrogen bonds with the organic silicon polymer, are adsorbed on the surface of the network structure, and are self-stacked, gradually expanding the network structure, prolonging the penetration time of the rust inhibitor, and further improving the anti-corrosion and anti-cracking performance of the concrete. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the anti-cracking and anti-corrosion concrete prepared in the following examples are as follows:

[0023] Cracking resistance: The examples and comparative examples were made into standard test blocks according to GB / T50081. After 28 days of pouring, the total cracking area of ​​the cracks on the standard test blocks was measured.

[0024] Anti-corrosion: Tested according to 7.1 fast chloride ion migration coefficient method in GB / T50082; tested against sulfate corrosion coefficient according to GB / T749.

[0025] Example 1

[0026] (1) Kitchen residues are sorted, bones are removed, and the residues are fed into a press, where they are pressed to a moisture content of 20 to obtain a wet material, 0.3 times the mass of cement and 0.9 times the mass of fly ash are added to the wet material, and the residues are fed into a crusher, where they are crushed to a particle size of 1 mm, and granulated to obtain an intermediate A with a diameter of 5 mm; the bacterial liquid and the intermediate A are mixed at a mass ratio of 1:1000, fermented at 37°C, 80 rpm, and a ventilation volume of 4 L / min for 48 h, dried at 100°C for 10 h, heated to 200°C, semi-carbonized for 4 h, and fed into an air flow mill, where the air flow is 200°C and a volume fraction of 15% carbon dioxide-nitrogen. , crushed for 20 minutes, taken out, activated at 400℃ for 20 minutes in a 15% volume fraction carbon dioxide-nitrogen atmosphere to obtain intermediate B; intermediate B and 15% mass fraction nitric acid solution were mixed in a mass ratio of 1:3, the ball-to-material ratio was 15:1, and the grinding was carried out at 150rpm for 10 minutes, and then a 4% mass fraction sodium nitrite aqueous solution of 3 times the mass of intermediate B was added, and the grinding was continued for 10 minutes, filtered, and dried at 100℃ for 6 hours to obtain an ultrafine filler; the bacterial liquid was composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content was 1×10 12 The powder feeding pressure of the air flow mill is 0.4MPa and the crushing pressure is 0.8MPa.

[0027] (2) Hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, peregal O-25, and deionized water were mixed in a mass ratio of 50:20:0.5:80, stirred at 600 rpm for 15 min, and homogenized at a pressure of 30 MPa for 1 min to obtain a pre-emulsion precursor;

[0028] (3) Under stirring at 300 rpm, add a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 50°C for 1 hour, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 50 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, and deionized water is 350:25:100:150:80:4:160.

[0029] Example 2

[0030] (1) Kitchen residues are sorted, bones are removed, and the residues are fed into a press, where they are pressed to a moisture content of 25% to obtain wet materials, 0.4 times the mass of cement and 1.2 times the mass of fly ash are added to the wet materials, and the residues are fed into a crusher, where they are crushed to a particle size of 2 mm, and granulated to obtain an intermediate A with a diameter of 8 mm; the bacterial liquid and the intermediate A are mixed at a mass ratio of 1:1000, fermented at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dried at 100°C for 10 h, heated to 220°C, semi-carbonized for 6 h, and fed into an air flow mill, where the air flow is 200°C and a volume fraction of 15% carbon dioxide-nitrogen Gas, crush for 25 minutes, take out, activate at 450℃ for 25 minutes in a 15% volume fraction carbon dioxide-nitrogen atmosphere to obtain intermediate B; mix intermediate B and 20% mass fraction nitric acid solution in a mass ratio of 1:3, grind at 200rpm for 18 minutes with a ball-to-material ratio of 15:1, add 4% mass fraction sodium nitrite aqueous solution 4 times the mass of intermediate B, continue grinding for 18 minutes, filter, and dry at 100℃ for 6 hours to obtain ultrafine filler; the bacterial solution is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 / mL; the powder feeding pressure of the airflow mill is 0.4MPa, and the crushing pressure is 0.9MPa;

[0031] (2) Hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, peregal O-25, and deionized water were mixed in a mass ratio of 50:25:0.5:89, stirred at 600 rpm for 22 min, and homogenized at a pressure of 30 MPa for 1 min to obtain a pre-emulsion precursor;

[0032] (3) Under stirring at 300 rpm, add a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 68°C for 1.5 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 60 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, and deionized water is 420:30:120:250:100:6:170.

[0033] Example 3

[0034] (1) Kitchen residues are sorted, bones are removed, and the residues are fed into a press and pressed to a moisture content of 30% to obtain wet materials. Cement 0.5 times the mass of the wet materials and fly ash 1.6 times the mass of the wet materials are added, and the residues are fed into a crusher and crushed to a particle size of 3 mm. The intermediate A with a diameter of 10 mm is obtained by granulation. The bacterial liquid and the intermediate A are mixed at a mass ratio of 1:1000, fermented at 55°C, 80 rpm, and a ventilation volume of 8 L / min for 72 h, dried at 100°C for 10 h, heated to 250°C, semi-carbonized for 8 h, and fed into an air flow mill with an air flow of 200°C and a volume fraction of 15% carbon dioxide- The mixture was crushed with nitrogen for 30 minutes, and then taken out and activated at 500°C for 30 minutes in an atmosphere of 15% carbon dioxide-nitrogen by volume to obtain intermediate B; intermediate B and 35% nitric acid solution were mixed in a mass ratio of 1:3, and the ball-to-material ratio was 15:1. After grinding at 250rpm for 25 minutes, a 4% sodium nitrite aqueous solution with a mass fraction of 5 times that of intermediate B was added, and the grinding was continued for 25 minutes, filtered, and dried at 100°C for 6 hours to obtain an ultrafine filler; the bacterial solution was composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content was 9×10 12 The powder feeding pressure of the air flow mill is 0.4MPa and the crushing pressure is 1.0MPa.

[0035] (2) Hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, peregal O-25, and deionized water were mixed in a mass ratio of 50:30:0.5:95, stirred at 600 rpm for 30 min, and homogenized at a pressure of 30 MPa for 1 min to obtain a pre-emulsion precursor;

[0036] (3) Under stirring at 300 rpm, add a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 80°C for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 70 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, and deionized water is 550:35:150:320:120:8:180.

[0037] Comparative Example 1

[0038] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: sort the kitchen residues, remove the bones, enter the press, press to a moisture content of 25%, enter the crusher, crush to a particle size of 2 mm, and granulate to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A in a mass ratio of 1:1000, ferment at 43°C, 80rpm, and a ventilation volume of 6L / min for 56h, dry at 100°C for 10h, heat to 220°C, semi-carbonize for 6h, enter an air flow mill, and the air flow is 200°C with a volume fraction of 15% carbon dioxide-nitrogen, and grind into powder. After crushing for 25 minutes, take it out and activate it at 450℃ for 25 minutes in an atmosphere of 15% carbon dioxide-nitrogen by volume to obtain intermediate B; mix intermediate B and 20% nitric acid solution by mass ratio of 1:3, grind at 200rpm for 18 minutes with a ball-to-material ratio of 15:1, add 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of intermediate B, continue grinding for 18 minutes, filter, and dry at 100℃ for 6 hours to obtain ultrafine filler; the bacterial solution is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 The powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.9 MPa; the remaining steps are the same as those in Example 2.

[0039] Comparative Example 2

[0040] The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: sort the kitchen residues, remove the bones, enter the press, press to a moisture content of 25% to obtain a wet material, add 0.4 times the mass of cement and 1.2 times the mass of fly ash to the wet material, enter the crusher, crush to a particle size of 2 mm, and granulate to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment at 43°C, 80rpm, and a ventilation volume of 6L / min for 56h, dry at 100°C for 10h, heat to 800°C, carbonize for 3h, enter the air flow mill, and air flow is 200°C. The invention relates to a method for preparing an ultrafine filler. The method comprises the following steps: mixing the intermediate B and a nitric acid solution with a mass fraction of 20% at a mass ratio of 1:3, grinding the mixture at a ball-to-material ratio of 15:1 and 200 rpm for 18 minutes, adding a 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of the intermediate B, and continuing to grind for 18 minutes. The mixture is filtered and dried at 100°C for 6 hours to obtain an ultrafine filler. The bacterial solution is composed of white mold, lactic acid bacteria, white rot fungi and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 The powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.9 MPa; the remaining steps are the same as those in Example 2.

[0041] Comparative Example 3

[0042] The difference between Comparative Example 3 and Example 2 is that step (1) is changed to: sort the kitchen residues, remove the bones, enter the press, press to a moisture content of 25% to obtain a wet material, add 0.4 times the mass of cement and 1.2 times the mass of fly ash to the wet material, enter the crusher, crush to a particle size of 2 mm, and granulate to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dry at 100°C for 10 h, and then heat to 220°C. The mixture was semi-carbonized for 6 hours, activated at 450°C for 25 minutes in a carbon dioxide-nitrogen atmosphere with a volume fraction of 15%, and intermediate B was obtained; intermediate B and 20% nitric acid solution were mixed in a mass ratio of 1:3, the ball-to-material ratio was 15:1, and the mixture was ground at 200rpm for 18 minutes, and then a 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of intermediate B was added, and the grinding was continued for 18 minutes, filtered, and dried at 100°C for 6 hours to obtain an ultrafine filler; the bacterial solution was composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content was 5×10 12 The remaining steps are the same as those in Example 2.

[0043] Comparative Example 4

[0044] The difference between Comparative Example 4 and Example 2 is that step (1) is changed to: sort the kitchen residues, remove the bones, enter the press, press to a moisture content of 25% to obtain a wet material, add 0.4 times the mass of cement and 1.2 times the mass of fly ash to the wet material, enter the crusher, crush to a particle size of 2 mm, and granulate to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dry at 100°C for 10 h, heat to 220°C, and semi-carbonize. 6h, enter the air flow mill, the air flow is 200℃ with a volume fraction of 15% carbon dioxide-nitrogen, grind for 25min to obtain intermediate B; intermediate B and 20% nitric acid solution are mixed in a mass ratio of 1:3, the ball-to-material ratio is 15:1, and the grinding is carried out at 200rpm for 18min, and then a 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of intermediate B is added, and the grinding is continued for 18min, filtered, and dried at 100℃ for 6h to obtain an ultrafine filler; the bacterial liquid is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 The powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.9 MPa; the remaining steps are the same as those in Example 2.

[0045] Comparative Example 5

[0046] The difference between Comparative Example 5 and Example 2 is that step (1) is different. Step (1) is changed to: sort the kitchen residues, remove the bones, enter the press, press to a moisture content of 25% to obtain a wet material, add 0.4 times the mass of cement and 1.2 times the mass of fly ash to the wet material, enter the crusher, crush to a particle size of 2 mm, and granulate to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dry at 100°C for 10 h, and then heat to 220°C. , semi-carbonized for 6 hours, and then put into a jet mill, the airflow is 200℃ with a volume fraction of 15% carbon dioxide-nitrogen, after pulverizing for 25 minutes, take out, and activate at 450℃ for 25 minutes in an atmosphere of 15% carbon dioxide-nitrogen to obtain intermediate B; intermediate B and a 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of intermediate B are further ground for 18 minutes, filtered, and dried at 100℃ for 6 hours to obtain an ultrafine filler; the bacterial liquid is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 The powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.9 MPa; the remaining steps are the same as those in Example 2.

[0047] Comparative Example 6

[0048] The difference between Comparative Example 6 and Example 2 is that there is no step (1), and step (3) is changed to: under stirring at 300 rpm, add a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 68°C for 1.5 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the speed to 60 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, microsilica powder, and sodium nitrate, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, deionized water, and sodium nitrate is 420:30:120:250:6:170:3; the remaining steps are the same as Example 2.

[0049] Comparative Example 7

[0050] The difference between Comparative Example 7 and Example 2 is that there is no step (2), and step (3) is changed to: under stirring at 60 rpm, cement, ultrafine filler, and deionized water are added, and stirring is carried out for 5 minutes, and then coarse aggregate, microsilica powder, and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine are added, and stirring is carried out for 10 minutes to obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, cement, fine aggregate, ultrafine filler, microsilica powder, deionized water, and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine is 420:120:250:100:6:170:30; the remaining steps are the same as in Example 2.

[0051] Effect example

[0052] Table 1 below shows the performance analysis results of the anti-cracking and anti-corrosion concrete using Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.

[0053] Table 1

[0054]

[0055] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention utilizes kitchen residues, cement and fly ash through semi-carbonization to obtain an aggregate-like filler with apparent strength and certain toughness inside, which can improve the anti-cracking performance of concrete. Its surface has a porous structure. After being ground and modified by nitric acid, the content of surface active groups is increased. The inorganic rust inhibitor is used as a raw material and ground again to form an ultrafine particle size. At the same time, the inorganic rust inhibitor is fixed and filled in the holes, and the release of the inorganic rust inhibitor is effectively controlled to achieve the anti-corrosion effect of the concrete. In the process of preparing concrete, the present invention also adds a pre-emulsion precursor prepared by hexaethylcyclotrisiloxane and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine to form a tough network structure inside the aggregate and cement, thereby improving the anti-cracking performance of the concrete. The ultrafine filler is adsorbed on the surface of the network structure and self-stacked, thereby prolonging the penetration time of the rust inhibitor and further improving the anti-corrosion performance of the concrete.

[0056] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing crack-resistant and corrosion-resistant concrete, characterized in that: The method comprises the following preparation steps: (1) Kitchen residues are sorted, bones are removed, and the residues are fed into a press to obtain wet materials, cement of 0.3 to 0.5 times the mass of the wet materials and fly ash of 0.9 to 1.6 times the mass of the wet materials are added, and the residues are fed into a crusher to be crushed to a particle size of 1 to 3 mm, and granulated to obtain an intermediate A of 5 to 10 mm in diameter; the bacterial liquid and the intermediate A are mixed at a mass ratio of 1:1000, fermented at 37 to 55° C., 80 rpm, and a ventilation volume of 4 to 8 L / min for 48 to 72 h, dried at 100° C. for 10 h, and then heated to 200 to 250° C. , semi-carbonized for 4 to 8 hours, put into a jet mill, crushed for 20 to 30 minutes, taken out, activated at 400 to 500°C for 20 to 30 minutes in an atmosphere of 15% by volume carbon dioxide-nitrogen, to obtain intermediate B; intermediate B and nitric acid solution were mixed at a mass ratio of 1:3, the ball-to-material ratio was 15:1, and the grinding speed was 150 to 250 rpm for 10 to 25 minutes, and then a sodium nitrite aqueous solution 3 to 5 times the mass of intermediate B was added, and the grinding was continued for 10 to 25 minutes, filtered, and dried at 100°C for 6 hours to obtain an ultrafine filler; (2) Under stirring at 300 rpm, add the pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 50-80°C for 1-2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 50-70 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete.

2. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The press in step (1) presses the soil until the moisture content is between 20% and 30%.

3. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The bacterial solution in step (1) is composed of Geotrichum candidum, lactic acid bacteria, white rot fungi, and Aspergillus niger in a volume ratio of 1:1:1:1, and the bacterial content is (1-9)×10 12 Pieces / mL.

4. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The powder feeding pressure of the air flow mill in step (1) is 0.4 MPa, and the crushing pressure is 0.8-1.0 MPa.

5. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The airflow of the airflow mill in step (1) is 15% carbon dioxide-nitrogen at 200°C.

6. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The mass fraction of the nitric acid solution in step (1) is 15-35%.

7. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The mass fraction of the sodium nitrite aqueous solution in step (1) is 4%.

8. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The preparation method of the pre-emulsion precursor in step (2) is: hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, perchlorate O-25, and deionized water are mixed in a mass ratio of 50:20:0.5:80 to 50:30:0.5:95, stirred at 600 rpm for 15 to 30 minutes, and homogenized at a pressure of 30 MPa for 1 minute.

9. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder and deionized water in step (2) is 350-550:25-35:100-150:150-320:80-120:4-8:160-180.

10. The method for preparing crack-resistant and corrosion-resistant concrete according to claim 1, characterized in that: The particle size of the microsilica powder in step (2) is 0.1-0.5 μm, and the silicon content of the microsilica powder is more than 93%.

Citation Information

Patent Citations

  • Anti-cracking / corrosion-resistant concrete and preparation method and application thereof, concrete pressure pipe and preparation method thereof

    CN109320167A

  • Method and system for preparing filler from aluminum sludge and kitchen garbage

    CN116282502A